A Hybrid Method for Low-Resource Named Entity Recognition - Do Minh Duc; Quan Xuan Truong; Viet Tran Hong; Le Hoang Anh; Mac Thi Minh Tra; Nguyen Van Thuy; Le Hai Ha; Vinh Nguyen Van (Journal of Applied Data Sciences, 2026)
Named Entity Recognition (NER) is a critical component of Natural Language Processing with diverse applications in information extraction and conversational AI. However, NER in specific domains for low-resource languages faces challenges such as limited annotated data and heterogeneous label sets. This study addresses these issues by proposing a hybrid neurosymbolic framework that integrates rule-based processing with deep learning models for Vietnamese NER. The core idea involves a two-stage pipeline: first, a rule-based component reduces label complexity by grouping relational and special categories; second, pre-trained language models are fine-tuned for high-precision extraction. A post-processing module is then utilized to restore fine-grained labels, preserving expressiveness for application-level usability. To mitigate data scarcity, a scalable data augmentation strategy leveraging Large Language Models (LLMs) is introduced to expand the label set without full re-annotation—a significant novelty of this work. The effectiveness of this method was evaluated across five specific-domain datasets, including logistics, wildlife, and healthcare. Experimental results demonstrate substantial improvements over strong RoBERTa-based baselines. Specifically, the proposed system achieved F1 scores of 90% in Customer Service (up from 83%), 84% in GAM (up from 73%), 83% in AI Fluent (up from 80%), 94% in PhoNER_Covid19 (up from 91%), and 60% in Rare Wildlife (up from 36%). These findings confirm that the hybrid approach effectively captures the linguistic complexity of Vietnamese and contextual nuances in specialized domains, offering a robust contribution to low-resource NER research.